Plant breeding advancements with “CRISPR-Cas” genome editing technologies will assist future food security - AHMAD, M. (Frontiers in Plant Science, 2023)
Genome editing techniques are being used to modify plant breeding, which might increase food production sustainably by 2050. A product made feasible by genome editing is becoming better known, because of looser regulation and widespread acceptance. The world's population and food supply would never have increased proportionally under current farming practices. The development of plants and food production has been greatly impacted by global warming and climate change. Therefore, minimizing these effects is crucial for agricultural production that is sustainable. Crops are becoming more resilient to abiotic stress because of sophisticated agricultural practices and a better understanding of the abiotic stress response mechanism. Both conventional and molecular breeding techniques have been used to create viable crop types. Both processes are time-consuming. Recently, plant breeders have shown an interest in genome editing approaches for genetic manipulation that use (CRISPR-CAS,9). Prospective food availability depends on the development of flowering plants with the right characteristics. A completely new era in plant breeding has begun because of the revolution in genome editing techniques based on the CRISPR/CRISPR-associated nuclease 9 (Cas9) systems. All plants may effectively target a particular gene or group of loci using Cas9 and the single-guide RNA (sgRNA). Cas9-CRISPRcan thereby save time and labour compared to conventional breeding methods. An easy, quick, and efficient method for directly altering the genetic sequences in cells is with the CRISPR and Cas9 systems. A number of cells can be addressed for gene breakdown and modification using the Cas9-CRISPR system, which was created from elements of the earliest known bacterial immune system. RNA sequences direct endonuclease cleavage specificity in the Cas9-CRISPR system. By modifying the guide (g-RNA) sequence and delivering it to a target cell together with the Cas9 endonuclease, cutting can be directed to almost any genomic region. We review current Cas9-CRISPR plant research discoveries, look into prospective crop breeding applications, and forecast probable future developments and strategies for achieving food security beyond 2050.